Invasive Hemodynamic Monitoring in Cardiogenic Shock Is Associated With Lower In‐Hospital Mortality - Mohammed Osman (Wiley, 2021)
Background There is increasing utilization of cardiogenic shock treatment algorithms. The cornerstone of these algorithms is the use of invasive hemodynamic monitoring (IHM). We sought to compare the in‐hospital outcomes in patients who received IHM versus no IHM in a real‐world contemporary database. Methods and Results Patients with cardiogenic shock admitted during October 1, 2015 to December 31, 2018, were identified from the National Inpatient Sample. Among this group, we compared the outcomes among patients who received IHM versus no IHM. The primary end point was in‐hospital mortality. Secondary end points included vascular complications, major bleeding, need for renal replacement therapy, length of stay, cost of hospitalization, and rate of utilization of left ventricular assist devices and heart transplantation. Propensity score matching was used for covariate adjustment. A total of 394 635 (IHM=62 565; no IHM=332 070) patients were included. After propensity score matching, 2 well‐matched groups were compared (IHM=62 220; no IHM=62 220). The IHM group had lower in‐hospital mortality (24.1% versus 30.6%, P<0.01), higher percentages of left ventricular assist devices (4.4% versus 1.3%, P<0.01) and heart transplantation (1.3% versus 0.7%, P<0.01) utilization, longer length of hospitalization and higher costs. There was no difference between the 2 groups in terms of vascular complications, major bleeding, and the need for renal replacement therapy. Conclusions Among patients with cardiogenic shock, the use of IHM is associated with a reduction in in‐hospital mortality and increased utilization of advanced heart failure therapies. Due to the observational nature of the current study, the results should be considered hypothesis‐generating, and future prospective studies confirming these findings are needed.